Retroactive Attentional Shifts Predict Performance in a Working Memory Task: Evidence by Lateralized EEG Patterns - Göddertz, Anna; Klatt, Laura-Isabelle; Mertes, Christine; Schneider, Daniel (Frontiers in Human Neuroscience, 2018)
Shifts of attention within working memory based on retroactive (retro-) cues were shown to facilitate performance in working memory tasks. While posterior asymmetries in the EEG, e.g. contralateral delay activity (CDA), can be used to study the active storage of lateralized working memory representations, results on the relation of such asymmetric effects to retro-cue benefits were so far inconclusive. We recorded EEG in a retro-cue working memory task with lateralized items and a continuous performance response. Following either a selective or neutral retro-cue, participants adjusted the orientation of a central memory probe to the cued item. Selective retro-cues elicited an early posterior contralateral negativity (PCN), anterior directing attention negativity (ADAN), and a later modulation of CDA indicating that active storage was concentrated on the cued information. By dividing all trials into three within-condition performance quantiles, we could further show that high working memory accuracy was associated with a sustained increase of the CDA effect following the retro-cue. These results suggest that focusing resources on the active storage of relevant representations is an important factor regarding retro-cue benefits in working memory tasks.